STRENGTH AND DEFORMABILITY TALEBETONNYH DESIGNS (Municipal economy of cities. Series: «Economy science», 2013)
A method of strength calculation of rectangular section of steel-concrete columns depending on the process of longitudinal loading has been developed. Theoretical and experimental data have been compared. Cite experiment and theoretical investigation steel concrete constructions depending on the process of longitudinal loading has been developed and method their calculation. There was executed the experimental and theoretical researches of the steel-concrete elements, working by center compression.